Ecotourism Hazard Mapping in Torean Trail, Mount Rinjani National Park, North Lombok District - Muntasib, E.K.S Harini; Aditya, Mahendra Dimas; Soekmadi, Rinekso (Media Konservasi, 2023)
Mount Rinjani is a mountain located in Mount Rinjani National Park and is popular as a hiking tourist destination. The Torean Trail is one of 6 hiking trails on Mount Rinjani that has potential ecotourism hazards, namely physical hazards, biological hazards, and human activity hazards. The purpose of the study was to identify and assess potential hazards in hiking activities on the Torean trail based on physical, biological and human activity aspects. The type of data collected is data on potential physical, biological and human activity hazards that may pose a risk, the incidence of accidents, and the location where the hazards are found. Data were collected through literature study, field observations, and interviews. There are 3 kinds of hazards found in the Toreab Trail, namely physical hazards, biological hazards, and human hazards. These hazards can threaten tourists when hiking through the Torean Trail.